NORMATIVE AND LEGAL REGULATION OF ECONOMIC AND LEGAL RELATIONS IN MODERN CONDITIONS OF STATE-BUILDING: REALITIES AND PROSPECTS OF DEVELOPMENT - Moroz, Viktor; Polyatsko, Anna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: the article is devoted to the analysis of realities and prospects of the development of normative regulation of economic and legal relations in modern conditions of state-building. Methods of research: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: analyzed conceptual aspects of legal regulation of economic and legal relations in modern conditions of state-building, problems of introduction of relevant legal mechanisms of regulation of economic and legal relations in the legislation of Ukraine, genesis of normative and legal regulation of economic and legal relations, carried out comparative analysis. According to the results of the analysis within the article, the conclusions were drawn that in the conditions of modern economic development, economic relations have undergone significant changes. In particular, there were new components of such relations: new participants of economic relations (virtual enterprises) and objects (virtual), electronic form of connections, including contracts, as well as related problems of the legal regime of the mentioned objects, the responsibility of new participants in economic relations. Characteristic signs of new economic realities indicate the need to reflect at the level of legislation the specifics of economic relations in the modern economy. Systemic legal support of modern economic relations is associated with the full-scale formation of the system of legislation, taking into account the realities of today and the prospects of economic development, which should be based on the priorities of integration into the EU single market and take into account the sectoral specifics of domestic production. Ukraine’s involvement in the processes of globalization of the economic space requires the development of conceptual principles for the modernization of the domestic economy and the creation of proper legal support for relations that consist in the process of forming and further functioning of the modern economy. Discussion: the analysis of normative regulation of economic and legal relations in modern conditions of state-building is carried out.